Digital Innovation in the Specialty Coffee Market: Revolutionizing Business and Competitive Advantage - Kurniawan Arif Maspul (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
Digital innovation has transformed the specialty coffee sector, altering business models and presenting industry participants with a competitive advantage. This abstract investigates the transformative effect of digital innovation in the specialty coffee sector, looking at how it affects business practices and market dynamics. This study illustrates how digital innovation has transformed customer experiences, enhanced operational efficiency, and supported sustainability practices through a detailed review of case studies and industry data. The findings emphasize major technologies that are driving this transition, such as remote sensing, blockchain, and data analytics, as well as successful methods employed by coffee-producing and consuming countries. The specialty coffee business can unleash new development prospects, build worldwide relationships, and stay ahead in a fast-developing market by adopting digital innovation It is a resource for industry professionals who want to employ digital innovation to gain a competitive advantage and generate long-term business growth in the specialty coffee market.